Meningkatkan Motivasi dan Hasil Belajar Siswa dengan Metode Tutor Sebaya pada Pembelajaran Remedial - Kaspani, Utik; Windyariani, Sistiana; Setiono (FKIP Universitas Muhammadiyah Sukabumi, 2022)
Abstract : Results of Integrated Science learning students class VII 2 MTs. Nurul Huda Palabuhanratu is still below the KKM score (70). There needs to be an effort to improve student learning outcomes, one of which is the peer tutor method. This classroom0action0research0aims0to0determine the0increase0in motivation and cognitive learning outcomes of class VII 2 MTs students. Nurul Huda Palabuhanratu by applying the peer tutor strategy. The subjects0in0this0study werw students of class VII 2 MTs.Nurul Huda Palabuhanratu as many as 20 students. The data collected in the form of student learning outcomes, questionnaire results, and teacher observations. The research was conducted in one cycle with two meetings with the stages0of 0planning, 0implementing, 0observing0and0reflecting. 0The research was said to be successful with a value of ≥70 and a percentage of 85%. Whereas in the final test of cycle I, classical learning completeness has reached the percentage of achievement of 85%. Based on the result of the study, it was obtained that the average value of learning completeness was 79 with a score of students' motivation and response responses of 65.79% and 65%. From0these0iy0can0be concluded that action in the learning process with peer tutors can increase students learning motivation an increase student cognitive learning outcomes. Keywords: learning outcomes, peer tutoring, motivation